Scenario Study on Future Land Administration in the UNECE Region - United Nations Economic Commission for Europe (United Nations, 2022)
Decision-makers in the field of land administration need a broad understanding of emerging issues and developments that are expected to shape the future of the sector. To this end, the UNECE Working Party on Land Administration agreed to elaborate scenarios for future land administration and land management solutions. This study discusses the future scenarios for the land administration sector, based on the relative importance and anticipated impacts of global megatrends and drivers specifically related to the sector.